AKI Epidemiology and Outcomes: A Retrospective Cohort Study from the Prenephrology Era - Asmus, K. (Int J Nephrol, 2021)
BACKGROUND: Acute kidney injury substantially worsens the prognosis of hospitalized patients. The Brandenburg Medical School was founded in 2014, and a nephrology section was opened in summer 2017. The aim of the study was to analyze AKI epidemiology and outcomes in one of two university hospitals belonging to the medical school. The period of interest dated from January to December 2015. METHODS: The investigation was designed as a single-center, retrospective cohort study at the Brandenburg Hospital of the Brandenburg Medical School. All in-hospital patients treated between January and the end of December 2015 were included. AKI was defined as specified in the 2012 published KDIGO criteria (criteria 1 and 2). Four parameters were evaluated in particular: AKI incidence, in-hospital mortality, frequency of renal replacement therapy, and renal recovery during the stay at the hospital. RESULTS: A total number of 5,300 patients were included in the analysis. AKI was diagnosed in 490 subjects (10.1%). The in-hospital mortality was 26%. The following conditions/parameters significantly differed between survivors (s) and nonsurviving (ns) subjects: duration of in-hospital treatment (s > ns), AKI onset (outpatient vs. in-hospital) (outpatient in s > ns), dialysis due to AKI (s < ns), vasopressor administration (s < ns), and invasive ventilation (s < ns). 5.6% received dialysis therapy, and renal recovery occurred in 31% of all surviving AKI subjects. CONCLUSION: Both, the AKI incidence and the frequency of dialysis were lower than reported in the literature. However, fewer subjects recovered from AKI. These discrepant findings possibly result from the lack of prehospitalization creatinine values, the lack of follow-up data, and a generally lower awareness for the need to perform renal replacement therapy in AKI.